2013
DOI: 10.1002/jnr.23276
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate prevents cell death from prolonged exposure to glutamate in an in vitro model of human dopaminergic neurons

Abstract: Ascorbate (vitamin C) is a nonenzymatic antioxidant highly concentrated in the brain. In addition to mediating redox balance, ascorbate is linked to glutamate neurotransmission in the striatum, where it renders neuroprotection against excessive glutamate stimulation. Oxidative stress and glutamatergic overactivity are key biochemical features accompanying the loss of dopaminergic neurons in the substantia nigra that characterizes Parkinson's disease (PD). At present, it is not clear whether antiglutamate agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…Additional protocols used for differentiation may involve combinations of the above-mentioned methods, or a combination of 10 μM RA and 0.3-5 mM dibutyryl cyclic adenosine monophosphate (dbcAMP) [39, 40], or of 10 μM RA for 3 days and 80nM tissue plasminogen activator [41] or the protocol was not specified. Differentiation may also be caused by 200 ng/mL growth/differentiation factor 5 (GDF5) [42], recombinant bone morphogenetic protein 2 (BMP2) [42], staurosporine [43, 44] or 50 ng/mL glial cell line-derived neurotrophic factor (GDNF) [45]. The pros and cons of the differentiation of the SH-SY5Y cell line to obtain a relevant model for PD have been reviewed more extensively elsewhere [46].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional protocols used for differentiation may involve combinations of the above-mentioned methods, or a combination of 10 μM RA and 0.3-5 mM dibutyryl cyclic adenosine monophosphate (dbcAMP) [39, 40], or of 10 μM RA for 3 days and 80nM tissue plasminogen activator [41] or the protocol was not specified. Differentiation may also be caused by 200 ng/mL growth/differentiation factor 5 (GDF5) [42], recombinant bone morphogenetic protein 2 (BMP2) [42], staurosporine [43, 44] or 50 ng/mL glial cell line-derived neurotrophic factor (GDNF) [45]. The pros and cons of the differentiation of the SH-SY5Y cell line to obtain a relevant model for PD have been reviewed more extensively elsewhere [46].…”
Section: Main Textmentioning
confidence: 99%
“…One complementary strategy to study PD in cells is to interfere directly with one of these processes by administering specific compounds, with agonistic or antagonistic activity, such as hydrogen peroxide (oxidative stress), lactacystin/MG-123 (proteasome inhibitors), tunicamycin (N-glycosylation inhibitor, triggers ER stress), bafilomycin (inhibitor of vacuolar H + ATPase, leading to autophagy dysfunction), thapsigargin (inhibitor of the sarco/endoplasmic reticulum Ca 2 + ATPase, resulting in ER stress and autophagy inhibition), carbonyl cyanide m-chlorophenyl hydrazone (CCCP) (inhibitor of oxidative phosphorylation, leading to mitochondrial dysfunction), Conduritol B epoxide (CBE) (GBA inhibitor), or salsolinol/staurosporine (cell death). Intriguingly, staurosporine, a broad-spectrum kinase inhibitor, has been used in some PD-related publications to induce cell death [6472], while other publications have used it to induce DAergic differentiation and study PD-related features [43, 44]. Early studies on SH-SY5Y cells showed differentiation towards a neuronal phenotype upon treatment with staurosporine [73, 74], which later has been characterized as catecholaminergic-like [75].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis evaluating oxidative stress biomarkers confirmed decreased antioxidant capacity in the plasma of patients with Alzheimer’s disease, suggesting that antioxidant defenses are consumed more rapidly in these individuals [32]. Animal and cell culture studies offer additional evidence that supplementation with ASC not only ameliorates oxidative stress, but also mitigates the production of Aβ [3337]. Previously published data from our group show a significant increase in soluble Aβ 1–42 and Aβ 1–40 peptides in cortical tissue from SVCT2 +/− ; APP/PSEN1 mice at 6 months compared with APP/PSEN1 mice that have normal SVCT2 transporter expression, indicating that compromised ASC capacity increases the momentum of Alzheimer’s disease pathological processes [38].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical assessments for use of vitamin C are less in comparison to use of tocopherol. In vitro study has also suggested the protective effect of vitamin A in AD pathology as it could offer destabilizing effects to amyloid fibrils [145] . The use of carotenoid has also been suggested by Zhang et al (2002) [146] in PD pathology.…”
Section: Evidences For the Beneficial Use Of Antioxidants In Neurodegmentioning
confidence: 99%